PENGARUH TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN MANAJEMEN, DAN PENGENDALIAN INTERNAL TERHADAP TRANSPARANSI PELAPORAN KEUANGAN DAERAH (Studi Empiris Pada SKPD Kabupaten Indragiri Hulu) - Tryoandha Mashunri; Amries Rusli Tanjung; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine directly the influence of external pressure, environmental uncertainty, management commitment, and internal control over the application of transparency of local financial reporting. This research was conducted in Indragiri Hulu Regency. The population in this research is 25 SKPD of Indragiri Hulu Regency. The number of samples of this study was 46 respondents. The research method used in this research is purposive sampling, while the data processing method used in this research is path analysis using SPSS 24.00 software to process the data. The results of this study indicate that external pressure affects the implementation of local financial reporting with a significant value of 0.038 (<0.05). Environmental uncertainty affects the implementation of local financial reporting with significant value of 0.038 (<0.05). Management commitment has an effect on the implementation of local financial reporting with significant value equal to 0,027 (<0,05). And internal control affects the implementation of local financial reporting with significant value of 0.000 (<0,05).Keywords : external pressure, environmental uncertainty, management commitment, internal control, local financial reporting, transparency